Faktor-faktor yang Mempengaruhi Niat Wajib Pajak untuk Menggunakan E- Filing. - Wardani, Dewi Kusuma; Ambarwati, Harum (AKMENIKA, 2017)
The purpose of this study to examine the effect implementation of the perceived usefulness, perceived ease of use, perceived taxpayer satisfaction, perceived usefulness, volunteerism, and social factors on the intention taxpayers to use e-filing. This type of research is associative research. The population in this study is the entire corporate taxpayers who use e-filing in Yogyakarta as respondents. The data collection is done directly by using a questionnaire containing 44 items statement. While data analysis tools using multiple regression with SPSS version 16.0. The results showed that the perception variables usefulness and perceived ease of use have a significant effect on the intention taxpayers to use e-filing, while the perception of satisfaction of taxpayers, perceived usefulness, volunteerism, and social factors had no significant effect on the intention taxpayers to use e-filing.